The level of Insurance awareness among private school teachers in the capital's Secretariat Sana'a - Al-Khatari, Yasmine Yehia AbdelQader; Al-Sanabani, Eman Saleh (Journal of Educational and Psychological Sciences, 2023)
The curent research aimed to identify the level of insurance awareness among private school teachers in the capital's Secretariat- Sana'a, In addition, to identify thr differences in the level of insurance awareness among private school teachers to the variables of gender, marital status, qualification and insurance subscription, and the sample consisted of (528) private school teachers in the capital, Sana'a, of whom (130) were males, (398) were females, They were selected according to the random, descriptive method, and the insurance awareness scale was used, prepared by the researcher, and the validity and reliability were extracted, and the scale consisted of (45) items, all of which were positive with five alternatives, and a set of appropriate statistical methods were used to achieve the objectives of the research, The results showed an average level of insurance awareness among the respondents, where the average total insurance awareness among the sample was (2.81 out of 5), and statistically significant differences were found at the level of significance (0.05) in their level of insurance awareness according to the variable of marital status in favor of the married category and statistically significant differences according to the variable The qualification for the benefit of the university class also found statistically significant differences in the variable of insurance subscription in favor of the insured, and the absence of statistically significant differences in the level of insurance awareness according to the gender variable. Insurance culture by all available means.
Keywords: Insurance awareness; private school teachers; social Insurance